Feasibility Study of TiOx Encapsulation of Diamond Solution‐Gate Field‐Effect Transistor Metal Contacts for Miniature Biosensor Applications. Issue 23 (10th November 2020) - Falina, Shaili; Tanabe, Kyosuke; Iyama, Yutaro; Tadenuma, Kaito; Bi, Te; Chang, Yu Hao; Manaf, Asrulnizam Abd; Syamsul, Mohd; Kawarada, Hiroshi
Abstract : The feasibility of titanium oxide (TiO x ) encapsulation of the source/drain metal contacts of diamond solution‐gate field‐effect transistor (SGFET) for biosensor applications is explored. The SGFETs fabricated by this method show excellent FET characteristics. For comparison, the electrical characteristics performance of SGFET TiO x encapsulated devices with two different channel lengths of 100 and 1.5 μm is investigated. The miniature device with a channel length of 1.5 μm exhibits remarkable enhancement of the maximum output current and transconductance ( g m ) to 3000 μA mm −1 and 11.3 mS mm −1, respectively. Furthermore, the scaling g m behavior of diamond SGFETs is experimentally studied by means of the channel length for the first time. The g m is enhanced when the channel length is reduced. The double‐layer capacitance of the diamond SGFET devices with channel mobility of 6–11 cm 2 (V s) −1 is estimated to be 3–5 μF cm −2 across the channel length which is adequate for biosensor applications. Abstract : This article presents fabrication of diamond solution‐gate field‐effect transistor (SGFET) with native titanium oxide (TiO x ) source–drain passivation for miniaturization purpose. The smallest device is fabricated with channel length of 1.5 μm, and shows remarkable current–voltage characteristics and transconductance value. Diamond SGFET with TiO x exhibits its functionality in response to pH solution opening possibility to use it as biosensor.